ӨЗБЕК, ҚАРАҚАЛПАҚ ҲӘМ ТҮРКМЕН ТИЛЛЕРИНДЕ АЙЫРЫМ КИЙИМ-КЕНШЕК АТАМАЛАРЫНЫҢ ЭТИМОЛОГИЯСЫ ҲӘМ УҚСАСЛЫҚЛАРЫ ҲАҚҚЫНДА - Бегжанов, Х. (SCIENCE and SOCIETY, 2022)
In this article, the issues of etymology and function of some clothing nouns are comparatively analyzed on the example of the Uzbek, Karakalpak and Turkmen languages, and their commonalities and similarities are identified.